Fungal backpackers—the mycobiome of Ips typographus after more than 80 years of research - Popa, Flavius; Buse, Joern; Biedermann, Peter H. W.; Kowallik, Vienna (Frontiers in Microbiology, 2026)
The European spruce bark beetle, Ips typographus, primarily colonizes Norway spruce and plays a pivotal ecological and economic role across Eurasia. Over decades, numerous studies have identified fungal species associated with I. typographus to comprehend their composition and relationships with the beetle and its tree host. The literature reveals a complex, diverse, and dynamic fungal community posing challenges in identifying consistent patterns. To enhance our understanding of the relationships in this tri-trophic system, a comprehensive overview of fungal associates is required. In this meta-analysis, we summarize the fungal species that have been found in association with I. typographus. Across 58 studies conducted over the last 80 years, 712 fungal species have been documented. Among these, 14 phytopathogenic species have been consistently recorded throughout the beetle’s distribution range in Europe and Asia, therefore considered being part of its core mycobiome. A further 150 species were documented in only one part of the beetles’ distribution range, and were classified as potential members of the core mycobiome. A significant proportion of the fungal assemblages were identified as passively associated species, constituting 77% of the total. We emphasize and engage in a critical discussion of the biases reflected in this data set, specifically those arising from the scientific methods employed and the sampled geographic areas. The majority of studies incorporated within this meta-analysis (n = 52) are based on conventional fungal culturing techniques with few recent publications (n = 6) incorporating modern molecular methods. At this point, the data suggest that the integration and complementary use of both methods may provide a more comprehensive representation of the mycobiome. Most studies have focused on Central and Northern Europe, with only six in Asia, leading to a significant data imbalance across the beetle’s range. Hence, the data here provide a snapshot of current research, with expectations for further development with future studies. This identified diverse array of fungi within the beetle’s mycobiome underscores the dynamic interactions between host trees, bark beetles, and their associated fungal community, highlighting their crucial roles in the beetle’s ecological success and illustrating its deep integration into a complex fungal ecosystem.